Anaplastic Pleomorphic Xanthoastrocytoma Presenting with Musical Hallucination - Oreoluwa Oladiran; Ifeanyi Nwosu; Steve Obanor; Chinyere Ogbonna-Nwosu; Brian Le (Case Reports in Neurological Medicine)
Musical hallucinations are a relatively rare form of auditory hallucination characterized by hearing of music in the absence of any external stimuli. This phenomenon has been linked to both psychiatric and structural lesions. We present the case of a previously healthy young male whose presentation with musical hallucinations led to the diagnosis of a rare tumour, anaplastic pleomorphic xanthoastrocytoma.